PEMIKIRAN MAHMUD SHALTUT TENTANG HUKUM OBLIGASI - Aqidatul Qomariyah (Maliyah : Jurnal Hukum Bisnis Islam, 2013)
Bonds are debt instruments conditional agreement that all such bonds should be described in the prospectus. In Islam debts agreement required to be stated in a letter of agreement but prohibited reduce debt or any additional terms of the agreement the debts. Mahmud Shaltut allow bond in urgent situations to meet a need. Where there is no other way to meet a need that, but just by holding bonds. Because if not in urgent situations, it may not hold government bonds. Nevertheless, Mahmud Shaltut provide requirements, that to estimate the urgent need to the degree of emergency and maslahah, should be in consideration legal experts, economists, and experts in the shari'ah 'at. The legal basis used by Mahmud Shaltut in digging permissibility Bonds with an approach al-hajah, al-darurat and al-maslahah.